Sore losers? The costs of intra-party democracy. (July 2019) - Cross, William; Pruysers, Scott
Drawing upon the 'satisfaction with democracy' and 'divisive primary' literatures, this article examines how losers of intra-party elections respond to defeat and the consequences that these choices have on party organization and strength. In other words, do losers of intra-party elections continue to support the party or do they, like losers of general elections, feel less satisfied with democracy and withdraw their support (or even 'exit' the party)? Exploring rates of membership activism and satisfaction from a recent study of Canadian party members, this article demonstrates that losers of intra-party elections are more likely to exit the party, significantly less likely to remain active and engaged in party politics, and significantly more likely to report dissatisfaction with party membership. These findings suggest that parties must find a way of keeping losers engaged with the party.